Optical Properties of Toluene-soluble Carbon Dots Prepared from Laser-ablated Coconut Fiber - Isnaeni, Isnaeni; Suliyanti, Maria Margaretha; Shiddiq, Muhandis; Sambudi, Nonny Soraya (UI Scholars Hub, 2019)
In this study, we used laser ablation to fabricate toluene-soluble carbon nanoparticles from coconut fiber. In response to excitations at various wavelengths, the fabricated carbon nanoparticles exhibit three distinctive emission peaks at wavelengths of 300 nm, 440 nm, and 540 nm. These three emission peaks correspond to the  orbital state,  orbital state, and surface state, respectively. Photoluminescence excitation measurements indicate a high probability of energy transfer between the surface state and  orbital state, whereas the  orbital state is likely independent of the other states. The results of time-resolved photoluminescence measurements indicate that electrons are likely to remain longer in higher-energy states. Given that the carbon dots fabricated in this study were made from natural resources, these findings may find application in photonic devices that feature tunable emissions.